PENERAPAN VECM DALAM MENGIDENTIFIKASI PENGARUH CURAH HUJAN DAN LUAS LAHAN TERHADAP PRODUKSI KOPI DI SUMATERA SELATAN - Habill Putra Sangnandha; Wellie Sulistijanti (EPSILON: JURNAL MATEMATIKA MURNI DAN TERAPAN, 2025)
Coffee production in South Sumatra Province plays an important role in Indonesia’s economy, both as a source of foreign exchange and as a livelihood for farmers. During the 2020–2023 period, coffee production exhibited fluctuations that reflected instability and were suspected to be influenced by environmental factors such as rainfall and land area. This study aims to analyze the influence of rainfall and land area on coffee production using the Vector Error Correction Model (VECM), which is capable of examining both short-term and long-term relationships among cointegrated time series variables. The data used consist of monthly records of coffee production, land area, and rainfall obtained from the Central Bureau of Statistics for the 2020–2023 period. The analysis was conducted through a series of statistical tests, including stationarity testing, cointegration, determination of optimal lag, VECM estimation, Granger causality test, as well as impulse response function (IRF) and variance decomposition (VD). The results reveal the existence of a long-term relationship among the variables, where rainfall significantly affects coffee production, while land area does not show a meaningful effect. The VD analysis also emphasizes that rainfall’s contribution to production variation increases up to 10% in the long term, while the applied model is validated through the Portmanteau test. These findings confirm that climatic factors, particularly rainfall, play an essential role in maintaining the stability and sustainability of coffee production in South Sumatra.